Negative electrode mixture, method for manufacturing the negative electrode mixture, and all-solid-state battery
The negative electrode composite material with a LiBH4 coating layer addresses the issue of resistance and degradation in sulfide solid electrolytes, enhancing the performance of all-solid-state batteries by maintaining ionic conductivity and improving cycle characteristics.
Patent Information
- Application Number
- JP2023096767
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2024-12-25
- Estimated Expiration
- 2043-06-13
Smart Images

Figure 2024178553000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a negative electrode mixture, a method for producing the negative electrode mixture, and an all-solid-state battery. [Background technology]
[0002] An all-solid-state battery is a battery that has a solid electrolyte layer between a positive electrode active material layer and a negative electrode active material layer, and has the advantage that it is easier to simplify safety devices compared to liquid batteries that have an electrolyte solution containing a flammable organic solvent. In particular, all-solid-state batteries using sulfide-based solid electrolytes have been actively researched in recent years due to their high ionic conductivity and good moldability. In addition, the addition of additives to improve the conductivity of the solid electrolyte is also being considered.
[0003] For example, Patent Document 1 describes a solid electrolyte made of sulfide and LiBH 4 and an all-solid-state battery including the solid electrolyte. Patent Document 2 discloses a method for producing an all-solid-state battery including a boron hydride compound as a solid electrolyte.
[0004] However, all-solid-state batteries face challenges, such as improving cycle life and output, and in addition to improving the ionic conductivity of the solid electrolyte, measures such as reducing the resistance of the electrode layer and suppressing material degradation are also required. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2016-134316 A [Patent Document 2] International Publication No. 2019 / 078130 Summary of the Invention [Problem to be solved by the invention]
[0006] In regard to the above point, although the sulfide solid electrolyte exhibits good ionic conductivity, it is easily reduced, and there is a risk that a deteriorated layer will be formed on the surface of the negative electrode active material in contact with the sulfide solid electrolyte, which may increase the resistance.
[0007] The present disclosure has been made in consideration of the above-mentioned circumstances, and has as its main object to provide a negative electrode mixture capable of suppressing an increase in resistance. [Means for solving the problem]
[0008] [1] A negative electrode composite material for use in an all-solid-state battery includes a coated negative electrode active material and a sulfide solid electrolyte, the coated negative electrode active material has a negative electrode active material and a coating layer that coats at least a portion of a surface of the negative electrode active material, and the coating layer is LiBH 4 and a borohydride solid electrolyte containing LiX, where X is selected from Cl, Br, or I.
[0009] [2] The negative electrode mixture according to [1], wherein the coated negative electrode active material contains graphite as the negative electrode active material.
[0010] [3] The negative electrode mixture according to [1] or [2], wherein in the coated negative electrode active material, a ratio of the boron hydride solid electrolyte to a total of the negative electrode active material and the boron hydride solid electrolyte is 0.8 vol.% or more and 22 vol.% or less.
[0011] [4] The negative electrode mixture according to any one of [1] to [3], wherein in the coated negative electrode active material, a ratio of the boron hydride solid electrolyte to a total of the negative electrode active material and the boron hydride solid electrolyte is 1.5 vol% or more and 15 vol% or less.
[0012] [5] The negative electrode mixture according to any one of [1] to [4], wherein the boron hydride solid electrolyte contains at least LiCl as the LiX.
[0013] [6] The negative electrode mixture according to any one of [1] to [5], wherein the sulfide solid electrolyte is an argyrodite-type sulfide solid electrolyte.
[0014] [7] [1] to [6], the method for producing a negative electrode composite according to any one of the above [1] to [6], further comprising: a coating step of obtaining the coated negative electrode active material; and a mixing step of mixing the coated negative electrode active material and the sulfide solid electrolyte to obtain the negative electrode composite, wherein the coating step is performed by mixing the LiBH 4 and a precursor layer-forming process of applying a precursor solution containing the LiX to a surface of the negative electrode active material and drying the negative electrode active material coated with the precursor solution to form a precursor layer, and a coating layer-forming process of heating the precursor layer to form a coating layer containing the borohydride solid electrolyte.
[0015] [8] An all-solid-state battery having a positive electrode active material layer, a negative electrode active material layer, and a solid electrolyte layer disposed between the positive electrode active material layer and the negative electrode active material layer, wherein the negative electrode active material layer contains the negative electrode mixture according to any one of [1] to [6]. Effect of the Invention
[0016] The present disclosure has an effect of providing a negative electrode composite material capable of suppressing an increase in resistance. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 is a schematic cross-sectional view illustrating a coated negative electrode active material according to the present disclosure. [Diagram 2] FIG. 1 is a schematic cross-sectional view illustrating an all-solid-state battery according to the present disclosure. [Diagram 3] 1 is a graph showing the relationship between the amount of coating material and the capacity maintenance rate in Examples 1 to 4 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The negative electrode composite, the method for producing the negative electrode composite, and the all-solid-state battery according to the present disclosure will be described in detail below.
[0019] A. Negative electrode mixture The negative electrode mixture in the present disclosure is a negative electrode mixture for use in an all-solid-state battery, and contains a coated negative electrode active material and a sulfide solid electrolyte. The coated negative electrode active material has a negative electrode active material and a coating layer that coats at least a portion of the surface of the negative electrode active material, and the coating layer is LiBH 4 and a boron hydride solid electrolyte containing LiX (X is selected from Cl, Br, or I). In this disclosure, the boron hydride solid electrolyte in the coating layer may be referred to as solid electrolyte A (SE-A), and the sulfide solid electrolyte in the negative electrode mixture may be referred to as solid electrolyte B (SE-B). In this specification, the "surface" of the negative electrode active material includes not only the outer surface of the negative electrode active material (negative electrode active material particles), but also a portion that can come into contact with a liquid such as a precursor solution described below.
[0020] According to the present disclosure, since the coating layer that coats the negative electrode active material contains a predetermined boron hydride solid electrolyte, an increase in resistance can be suppressed in the negative electrode mixture.
[0021] As described above, although the sulfide solid electrolyte has good ionic conductivity, it is easily reduced and there is a risk of a deterioration layer being formed on the surface of the negative electrode active material during repeated charging and discharging of the battery. In contrast, the negative electrode composite material in the present disclosure contains a predetermined coated negative electrode active material. In the coated negative electrode active material, the negative electrode active material is coated with a coating layer containing a predetermined borohydride solid electrolyte having good reduction resistance. Therefore, even if the battery is repeatedly charged and discharged, the formation of a deterioration layer is suppressed, the increase in resistance can be suppressed, and the cycle characteristics of the battery can be improved. In addition, since the coated negative electrode active material contains a sulfide solid electrolyte having good ionic conductivity, the negative electrode composite material can suppress the initial resistance. Furthermore, when a deterioration layer is formed, the movement of carrier ions such as Li ions may be hindered and the ionic conductivity may decrease, but the negative electrode composite material in the present disclosure has the advantage that the formation of a deterioration layer is suppressed, thereby suppressing the decrease in ionic conductivity.
[0022] 1.Coated negative electrode active material Fig. 1 is a schematic cross-sectional view illustrating a coated negative electrode active material according to the present disclosure. As shown in Fig. 1, the coated negative electrode active material 1 has a negative electrode active material 2 and a coating layer 3 that coats at least a part of the surface of the negative electrode active material. The coating layer 3 contains a predetermined borohydride solid electrolyte.
[0023] (1)Negative electrode active material The negative electrode active material in the present disclosure is not particularly limited as long as it functions as a negative electrode active material in a battery. Examples of the negative electrode active material include carbon-based active materials such as natural graphite, artificial graphite, graphene, hard carbon, and soft carbon; Nb 2 O 5 , Li 4 Ti 5 O 12 Examples of the active material include oxide active materials such as SiO and In, Al, Si, Sn, and alloys of these metals. Among these, graphite is preferable. The negative electrode active material may be one type or two or more types.
[0024] The negative electrode active material may be in the form of, for example, particles. The negative electrode active material may be in the form of primary particles or secondary particles.
[0025] Average particle size of the negative electrode active material (D 50 ) is, for example, 10 nm or more, may be 100 nm or more, may be 500 nm or more, may be 1 μm or more, or may be 5 μm or more. On the other hand, the average particle diameter (D 50 ) is, for example, 50 μm or less, may be 40 μm or less, may be 30 μm or less, may be 25 μm or less, or may be 20 μm or less. 50 ) refers to the cumulative 50% particle size in the volume-based particle size distribution measured by a laser diffraction particle size distribution analyzer. 50 The average particle size (D) may be the average particle size of primary particles or the average particle size of secondary particles. 50 ) refers to the cumulative 50% particle size in the volume-based particle size distribution measured with a laser diffraction particle size analyzer.
[0026] (2) Covering layer The coating layer in the present disclosure covers at least a part of the surface of the negative electrode active material and is 4 and a borohydride solid electrolyte containing LiX (X is selected from Cl, Br, or I). The "surface" is as described above, and the coating layer usually covers at least a portion of the outer surface of the negative electrode active material.
[0027] The boron hydride solid electrolyte is, for example, αLiBH 4 The composition is represented by 3LiBH 3LiX (X is at least one selected from Cl, Br, and I). α is, for example, a number between 1 and 5, and X is as described above. In particular, the composition of the boron hydride solid electrolyte is 3LiBH 4 - It is preferably represented by LiX.
[0028] The boron hydride solid electrolyte may contain only one of LiCl, LiBr and LiI as the LiX, or may contain two or more of them. In particular, the boron hydride solid electrolyte preferably contains LiCl as the LiX. For example, when the boron hydride solid electrolyte contains two or more LiX, the proportion of LiCl in all LiX is preferably 50% or more.
[0029] The boron hydride solid electrolyte is LiBH 4 and LiX solid solutions are preferred.
[0030] The coating layer may be a layer containing only the borohydride solid electrolyte as a material, or may be a layer containing other materials. In the latter case, the proportion of the borohydride solid electrolyte in the total materials constituting the coating layer is preferably 50% or more.
[0031] The coating layer may cover a part or the whole of the surface of the negative electrode active material. The coverage is, for example, 10% or more, 30% or more, 50% or more, 70% or more, or 90% or more. On the other hand, the coverage may be 100% or less. In the latter case, the coverage is, for example, 99% or less, 97% or less, 95% or less, or 93% or less.
[0032] The average thickness of the coating layer is, for example, 5 nm or more, may be 50 nm or more, or may be 100 nm or more, while the average thickness of the coating layer is, for example, 1000 nm or less, may be 500 nm or less, or may be 300 nm or less.
[0033] The coverage and average thickness can be determined, for example, by microscopic observation using a scanning electron microscope (SEM) and by XPS (X-ray photoelectron spectroscopy).
[0034] In the coated negative electrode active material, the ratio of the boron hydride solid electrolyte to the total of the negative electrode active material and the boron hydride solid electrolyte is, for example, 0.8% by volume or more, may be 1.5% by volume or more, may be 4% by volume or more, or may be 7% by volume or more. Meanwhile, the ratio is, for example, 22% by volume or less, may be 18% by volume or less, may be 15% by volume or less, or may be 11% by volume or less. In this specification, the ratio can also be referred to as "amount of coating material".
[0035] Furthermore, when the amount of coating material is expressed by weight, the amount of coating material is, for example, 0.5% by weight or more, optionally 1% by weight or more, optionally 3% by weight or more, or optionally 5% by weight or more, whereas the amount of coating material is, for example, 15% by weight or less, optionally 12% by weight or less, optionally 10% by weight or less, or optionally 7% by weight or less.
[0036] Here, the coating layer may cover the surface of the primary particles of the negative electrode active material, or may cover the surface of the secondary particles formed by agglomeration of the primary particles of the negative electrode active material. When the coated negative electrode active material is a secondary particle, the coating layer may cover the surfaces of both the primary particles and the secondary particles of the negative electrode active material. In this case, the boron hydride solid electrolyte can be considered to be disposed on the surface (surface of the secondary particles) and inside (surface of the primary particles) of the coated negative electrode active material. It is also preferable that the coating layer directly covers the negative electrode active material.
[0037] (3) Coated negative electrode active material The shape of the coated negative electrode active material is, for example, particulate. The coated negative electrode active material may be primary particles or secondary particles. The average particle size (D 50 ) is, for example, 10 nm or more and 50 μm or less. The above average particle size may be the average particle size of primary particles or the average particle size of secondary particles. 50 ) is as described above.
[0038] The ratio of the coated negative electrode active material in the negative electrode mixture is, for example, 40% by volume or more, or may be 50% by volume or more, or may be 70% by volume or more, while the ratio of the coated negative electrode active material is, for example, 90% by volume or less, or may be 80% by volume or less.
[0039] The method for producing the coated negative electrode active material will be described later.
[0040] 2.Sulfide solid electrolyte The sulfide solid electrolyte in the present disclosure is usually a solid electrolyte containing sulfur (S) as a main component of an anion element.
[0041] Examples of sulfide solid electrolytes include solid electrolytes containing Li, A (A is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga, and In), and S. The sulfide solid electrolyte may further contain at least one of O and halogen. Examples of halogen include F, Cl, Br, and I. The sulfide solid electrolyte may be glass (amorphous), glass ceramic, or crystalline.
[0042] As the sulfide solid electrolyte in the present disclosure, an argyrodite-type sulfide solid electrolyte is particularly preferred. The term "argyrodite-type sulfide solid electrolyte" refers to a sulfide solid electrolyte having an argyrodite-type crystal phase. Whether or not the electrolyte has an argyrodite-type crystal phase can be confirmed, for example, by performing an X-ray diffraction measurement (XRD measurement). In addition, the argyrodite-type sulfide solid electrolyte preferably has the argyrodite-type crystal phase as a main phase.
[0043] The composition of the argyrodite-type sulfide solid electrolyte is not particularly limited. For example, Li 7-y P.S. 6-y X′ y (X′ is a halogen element, and y is a number satisfying 0≦y≦2).
[0044] The sulfide solid electrolyte preferably has high ionic conductivity. The ionic conductivity at 25° C. is, for example, 0.5×10 -3 S / cm or more, 1×10 -3 S / cm or more, and 2×10 -3 It may be S / cm or more.
[0045] The shape of the sulfide solid electrolyte may be, for example, particulate. The average particle size (D 50 ) is, for example, 10 nm or more and 50 μm or less. 50 ) is as described above.
[0046] The proportion of the sulfide solid electrolyte in the negative electrode mixture is, for example, 10% by volume or more, or may be 30% by volume or more, or may be 50% by volume or more, while the proportion of the sulfide solid electrolyte is, for example, 60% by volume or less.
[0047] 3.Negative electrode composite material The negative electrode mixture in the present disclosure may further contain at least one of a conductive material and a binder.
[0048] Examples of conductive materials include carbon materials, metal particles, and conductive polymers. Examples of carbon materials include particulate carbon materials such as acetylene black (AB) and ketjen black (KB), and fibrous carbon materials such as carbon fibers, carbon nanotubes (CNT), and carbon nanofibers (CNF). Examples of binders include fluorine-containing binders such as polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE), rubber-based binders such as butadiene rubber, and acrylic binders.
[0049] The negative electrode mixture may be a negative electrode slurry containing a dispersion medium. Examples of the dispersion medium include organic solvents such as butyl butyrate, dibutyl ether, heptane, and tetrahydrofuran. The negative electrode slurry is applied to a substrate such as a current collector and dried to form a negative electrode active material layer containing the negative electrode mixture. On the other hand, the negative electrode mixture does not need to contain a dispersion medium.
[0050] The negative electrode mixture in this disclosure is typically used in the negative electrode active material layer of an all-solid-state battery, which is described in "C. All-solid-state batteries."
[0051] B. Method for manufacturing negative electrode mixture The method for producing the negative electrode mixture in the present disclosure includes a predetermined coating step and a mixing step.
[0052] 1. Coating process The coating step in the present disclosure is a step for obtaining the above-mentioned coated negative electrode active material, and includes a predetermined precursor layer forming treatment and coating layer forming treatment.
[0053] (1) Precursor layer formation process The precursor layer formation process was carried out using the LiBH 4 and a treatment for forming a precursor layer by applying a precursor solution containing the LiX to the surface of the negative electrode active material and drying the negative electrode active material to which the precursor solution has been applied.
[0054] The precursor solution was prepared by adding LiBH 4 A solvent containing LiX was added to the solvent containing LiBH 4 and LiX in a desired ratio. The solvent may be an organic solvent such as tetrahydrofuran (THF).
[0055] The coating method is not particularly limited, and for example, a method of immersing the negative electrode active material in the precursor solution and stirring it can be mentioned. In addition, the drying conditions such as drying temperature and drying time are not particularly limited as long as the solvent can be removed from the precursor solution. For example, the drying temperature is 80°C or more and 100°C or less, and the drying time is, for example, 5 minutes or more and 1 hour or less.
[0056] In the coating layer forming process described below, the above coating and drying may be repeated multiple times to form a coating layer having a desired thickness and coverage.
[0057] (2) Coating layer formation treatment The coating layer forming process in the present disclosure is a process of heating the precursor layer to form a coating layer. The coating layer is the same as that described in "A. Negative electrode composite material", and therefore will not be described here.
[0058] The heating temperature and heating time are not particularly limited as long as the desired coating layer can be formed. The heating temperature is, for example, 80° C. or higher and 150° C. or lower, and the heating time is, for example, 30 minutes or longer and 2 hours or shorter. Heating may also be performed under a reduced pressure environment such as a vacuum.
[0059] (3) Coated negative electrode active material The coated negative electrode active material is the same as that described in "A. Negative electrode mixture," and therefore will not be described here.
[0060] 2.Mixing process The mixing step in the present disclosure is a step of mixing the coated negative electrode active material and the sulfide solid electrolyte layer to obtain the negative electrode mixture.
[0061] The ratio of the coated negative electrode active material and the sulfide solid electrolyte is the same as that described in "A. Negative Electrode Mixture". In the mixing step, the coated negative electrode active material and the sulfide solid electrolyte may be mixed with at least one of a conductive material and a binder in the presence of a dispersion medium. The conductive material, the binder, and the dispersion medium are the same as those described in "A. Negative Electrode Mixture". The mixing method is not particularly limited and may be a conventionally known method.
[0062] 3.Negative electrode composite material The negative electrode composite produced by the above-mentioned method is similar to that described in "A. Negative electrode composite," and therefore will not be described here.
[0063] C. All-solid-state battery Fig. 2 is a schematic cross-sectional view illustrating an example of an all-solid-state battery in the present disclosure. The all-solid-state battery 10 shown in Fig. 2 has a positive electrode active material layer 11, a negative electrode active material layer 12, and a solid electrolyte layer 13 formed between the positive electrode active material layer 11 and the negative electrode active material layer 12, and the negative electrode active material layer 12 contains the above-mentioned negative electrode mixture. The all-solid-state battery 10 also has a positive electrode current collector 14 that collects current from the positive electrode active material layer 11, and a negative electrode current collector 15 that collects current from the negative electrode active material layer 12.
[0064] In the all-solid-state battery according to the present disclosure, the negative electrode active material layer contains the above-described negative electrode mixture, and therefore the all-solid-state battery has a good charge capacity retention rate.
[0065] 1.Negative electrode active material layer The negative electrode active material layer contains the above-mentioned negative electrode mixture. The negative electrode mixture is the same as that described in "A. Negative Electrode Mixture", so the description here is omitted. The thickness of the negative electrode active material layer is, for example, 0.1 μm or more and 1000 μm or less.
[0066] 2.Cathode active material layer The positive electrode active material layer contains at least a positive electrode active material. The positive electrode active material layer preferably contains at least one of a solid electrolyte, a conductive material, and a binder, as necessary. The positive electrode active material, the conductive material, and the binder may be conventionally known materials. The positive electrode active material layer preferably contains the above-mentioned sulfide solid electrolyte as a solid electrolyte. The thickness of the positive electrode active material layer is, for example, 0.1 μm or more and 1000 μm or less.
[0067] 3.Solid active material layer The solid electrolyte layer contains at least a solid electrolyte, and may contain a binder as necessary. The binder is as described above. The solid electrolyte is preferably the sulfide solid electrolyte described above. The thickness of the solid electrolyte layer is, for example, 0.1 μm or more and 1000 μm or less.
[0068] 4. Positive and negative electrode current collectors The material of the positive electrode current collector and the negative electrode current collector can be a conventionally known metal material, such as Al, SUS, Cu, or Ni.
[0069] 5.All-solid-state battery The all-solid-state battery in the present disclosure is typically a lithium-ion secondary battery. In addition, the use of the all-solid-state battery includes, for example, a power source for vehicles such as a hybrid electric vehicle (HEV), a plug-in hybrid electric vehicle (PHEV), an electric vehicle (BEV), a gasoline vehicle, and a diesel vehicle. In particular, it is preferable to use the all-solid-state battery as a driving power source for a hybrid electric vehicle (HEV), a plug-in hybrid electric vehicle (PHEV), or an electric vehicle (BEV). In addition, the all-solid-state battery may be used as a power source for a moving body other than a vehicle (for example, a train, a ship, or an aircraft), or may be used as a power source for an electric product such as an information processing device.
[0070] The present disclosure is not limited to the above-described embodiment. The above-described embodiment is merely an example, and any configuration that is substantially the same as the technical idea described in the claims of the present disclosure and that exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES
[0071] [Example 1] (Preparation of Coated Negative Electrode Active Material) LiBH 4 A tetrahydrofuran (THF) solution containing LiI and a THF solution containing LiBH 4 The molar ratio of LiI to LiBH was 3:1. 4 -LiI-containing THF solution was prepared. Next, the precursor solution was added to the negative electrode active material (spherical natural graphite, particle size 16 μm) and dried on a hot plate at 80°C. This operation was repeated several times. In this way, the amount of coating material (SE-A / (graphite+SE-A)) was adjusted to the value in Table 1. Then, vacuum drying was performed at 120°C for 1 hour. In this way, a coated negative electrode active material (coated graphite) was prepared.
[0072] (Preparation of negative electrode mixture) The Argyrodite-type sulfide-based solid electrolyte (SE-B) was added to the coated graphite and mixed thoroughly in a mortar. This produced a negative electrode composite. The amount of the Argyrodite-type sulfide-based solid electrolyte was adjusted so that the composition of the negative electrode composite would be the value shown in Table 1.
[0073] (Preparation of evaluation battery) A powder cell equipped with a cylindrical non-conductive ceramic guide with an inner diameter of 11.28 mm and a stainless steel current collector was prepared as a battery for evaluation (negative electrode half cell). Specifically, the above-mentioned negative electrode composite was put into the ceramic guide so that the graphite amount was 8 mg, and 0.1 g of an argyrodite-type sulfide-based solid electrolyte was put in, and pressed at 588 MPa to prepare a negative electrode active material layer and a separator layer. Then, an In-Li foil was placed on the separator layer as a counter electrode, and further pressed at 98 MPa. After that, it was restrained with a restraining jig. In this way, a battery for evaluation was prepared.
[0074] [Examples 2 to 4] A battery for evaluation was produced in the same manner as in Example 1, except that the coated negative electrode active material and the negative electrode mixture were prepared so that the amount of coating material and the composition of the negative electrode mixture were the values shown in Table 1.
[0075] [Comparative Example 1] In preparing the coated negative electrode active material, a borohydride solid electrolyte (3LiBH 4 A coated negative electrode active material was produced in the same manner as in Example 1, except that the above-mentioned argyrodite-type sulfide-based solid electrolyte was used instead of LiI. A battery for evaluation was produced in the same manner as in Example 1, except that a negative electrode mixture was produced using this coated negative electrode active material so that the composition was the value shown in Table 1.
[0076] [Comparative Example 2] Instead of the coated negative electrode active material, spherical natural graphite was used. The composition of the negative electrode mixture was determined as shown in Table 1. 4 The negative electrode mixture was prepared by carefully mixing the LiI and the argyrodite-type sulfide-based solid electrolyte together in a mortar. In other words, no coated graphite was prepared. A battery for evaluation was prepared in the same manner as in Example 1, except that the negative electrode mixture was used.
[0077] [evaluation] (Impedance measurement and capacity retention measurement) The cell resistance and charge capacity retention rate were evaluated as follows for the evaluation batteries of Examples 1 to 4 and Comparative Examples 1 and 2. The results are shown in Table 2 and FIG. First, the 1C current is 2.72mA / cm 2 0.1C-CCCV, 1.5-0.05V (vsLi + / Li) and 25°C, three charge / discharge cycles were performed (final charge / discharge). Thereafter, the battery was charged to 1.1 mAh, and impedance measurements were performed under conditions of a voltage width of 10 mV, a frequency range of 7 MHz to 0.01 Hz, and a temperature of 25° C., to measure the initial resistance. Then, at 60°C, 1.5-0.05V (vsLi + The battery was charged and discharged 20 times at 0.1 C-CCCV (1.1 mAh / Li), and then the impedance was measured again at 1.1 mAh charging. The resistance increase rate was calculated from the resistance after 20 cycles and the initial resistance. For each evaluation battery for which the resistance increase rate was calculated, + Charge rate tests were conducted at 1000mAh / Li) with CC charging at 0.1, 0.2, 0.3, and 0.5 C and CCCV discharging at 0.1 C. The charge capacity retention rate at 0.5 C was calculated based on the 0.1 C charge capacity.
[0078] [Table 1]
[0079] [Table 2]
[0080] As shown in Table 2, the resistance increase rate was significantly suppressed in all of the Examples, and the capacity retention rate was also good, compared to Comparative Examples 1 and 2. In addition, from the results of Examples 1 to 4 shown in Table 2 and Figures 3(a) and (b), it was confirmed that a better capacity retention rate could be obtained by adjusting the amount of coating material (wt% and vol%).
[0081] [Examples 5 and 6] A coated negative electrode active material was prepared using the coating material (borohydride solid electrolyte: SE-A) shown in Table 3, with the amount of coating material being the value in Table 3. A negative electrode composite and a battery for evaluation were produced and the above evaluations were carried out in the same manner as in Example 1, except that this coated negative electrode active material was used. The results are shown in Table 3. Note that although the resistance increase rate was negative in Example 6, the resistance increase rate was set to 0% for convenience.
[0082] [Table 3]
[0083] From Examples 1, 5 and 6, 3LiBH was used as the coating material. 4 When -LiCl was used, the resistance increase rate was most suppressed and the capacity retention rate was also good.
[0084] [Comparative Examples 3 to 5] A negative electrode composite was prepared by mixing uncoated graphite and a borohydride solid electrolyte (SE-A) shown in Table 4 in a mortar in the ratio shown in Table 4. A battery for evaluation was prepared in the same manner as in Example 1, except that this negative electrode composite was used. The initial resistance of the prepared battery for evaluation was measured by the method described above. The results are shown in Table 4.
[0085] [Table 4]
[0086] From Comparative Example 2 and Comparative Examples 3 to 5, it was confirmed that the initial resistance could be suppressed by using a sulfide solid electrolyte in the negative electrode mixture.
[0087] From the above results, it was confirmed that by using the negative electrode mixture according to the present disclosure, an increase in resistance can be suppressed and an all-solid-state battery with a good capacity retention rate can be obtained. [Explanation of symbols]
[0088] 1...Coated negative electrode active material 2...Negative electrode active material 3 … Coating layer 10 … All-solid-state battery 11 … Positive electrode active material layer 12 … Negative electrode active material layer 13 … Solid electrolyte layer 14 … Positive electrode current collector 15 … Negative electrode current collector
Claims
1. A negative electrode mixture for use in an all-solid-state battery, Contains a coated negative electrode active material and a sulfide solid electrolyte, The coated negative electrode active material has a negative electrode active material and a coating layer that coats at least a portion of a surface of the negative electrode active material, The coating layer is LiBH 4 and a borohydride solid electrolyte containing LiX, where X is selected from Cl, Br, or I.
2. The negative electrode mixture according to claim 1 , wherein the coated negative electrode active material contains graphite as the negative electrode active material.
3. 2. The negative electrode mixture according to claim 1, wherein in the coated negative electrode active material, a ratio of the boron hydride solid electrolyte to a total of the negative electrode active material and the boron hydride solid electrolyte is 0.8 vol.% or more and 22 vol.% or less.
4. 2. The negative electrode mixture according to claim 1, wherein in the coated negative electrode active material, a ratio of the boron hydride solid electrolyte to a total of the negative electrode active material and the boron hydride solid electrolyte is 1.5 vol% or more and 15 vol% or less.
5. 2. The negative electrode mixture according to claim 1, wherein the borohydride solid electrolyte contains LiCl as the LiX.
6. The negative electrode mixture according to claim 1 , wherein the sulfide solid electrolyte contains an argyrodite-type sulfide solid electrolyte.
7. A method for producing a negative electrode mixture according to any one of claims 1 to 6, A coating step of obtaining the coated negative electrode active material; A mixing step of mixing the coated negative electrode active material and the sulfide solid electrolyte to obtain the negative electrode mixture, The coating step includes: The LiBH 4 a precursor layer forming process for forming a precursor layer by applying a precursor solution containing the LiX to a surface of the negative electrode active material and drying the negative electrode active material to which the precursor solution has been applied; and a coating layer forming treatment of heating the precursor layer to form a coating layer containing the boron hydride solid electrolyte.
8. An all-solid-state battery having a positive electrode active material layer, a negative electrode active material layer, and a solid electrolyte layer disposed between the positive electrode active material layer and the negative electrode active material layer, An all-solid-state battery, wherein the negative electrode active material layer contains the negative electrode mixture according to any one of claims 1 to 6.
Citation Information
Patent Citations
Positive electrode active material, positive electrode, lithium ion secondary battery and method for producing positive electrode active material
JP2021174682A
Cathode materials and batteries
JP7756339B2
Coated active material, electrode material and battery
JP7788681B2
Solid electrolyte
JP2016134316A
Production method for all-solid-state battery
WO2019078130A1
Cited By
Active material and method for producing same, and electrode mixture, electrode, and battery including same
WO2025205592A1
